Effects of male quality on the reproduction of Tuta absoluta (Lepidoptera: Gelechiidae) - Oliveira, Sofia Pimenta de (2020)
Among several studies, there have been extremely interesting questions related to the reproductive aspects of many species. This occurs basically because reproduction itself, show different effects upon the mating system, for both male and female. Male ejaculate plays a key role in female reproduction and therefore to their offsprings. It is generally assumed that male age, male weight, and male mating status is a potentially important aspect affecting the mating biology of insects and causing many effects on female fitness. Differences related to the contribution of male ejaculate donation for females upon mating have been observed in several Lepidoptera species. In a laboratory experiment we examined the male condition and how it could impact female longevity and reproductive output. The parameters related to the male condition observed, were male pupal weight, male age (2, 4 and 6 days old) and male mating status (1, 2, 3 and 4 matings). We recorded for each female who has mated with these males, parameters such as fecundity, fertility, and longevity. We found that females who have mated to males of different ages, showed a decrease in fertility, fecundity, and longevity as the males get older. Also, the same pattern was observed for male mating status, whereas females' fecundity, fertility, and longevity decreased as the numbers of her previous partner increased. The male pupal weight did not show any effect upon fecundity and female longevity. However, it was significant for female fertility, which increases according to the increase in male pupal weight. These results demonstrated clear evidence of how the male condition impacts female longevity and reproductive aspects, highlighting the critical dependence of T. abosluta females upon their male partner condition . Keywords: Reproduction. Lepidoptera. Male condition.